Impact of the Transplant Acceleration Program (PAT-MA) Phase I on Transplant Indicators in Maranh㯬 Brazil: A Retrospective Study (London Journal of Medical and Health Research, 2025)
Introduction: In the context of public health, the efficiency of transplant programs is crucial to improving outcomes for patients on waiting lists. This study evaluated the impact of implementing the Transplant Acceleration Program (PAT-MA) at the Transplant Center of Maranho, Brazil.Objectives: The aim of this study was to assess the impact of PAT-MA implementation on key performance indicators of the Maranho Transplant Center, with a focus on improving the organization and effectiveness of the regional transplant system through structured management methodology.Methods: We conducted a retrospective observational study analyzing data from the Maranho Transplant Center before and after the first phase of PAT-MA as a quality improvement initiative, comparing the years 2022 and 2023. The indicators collected included: number of transplants performed, waiting list size, notifications per million population, effective donors per million, organ transplants per million, corneal transplants per million, and number of active CIHDOTTs and OPOs.Results: Following PAT-MA implementation, there was a reduction in the family refusal rate (from 67% to 63%), a decrease in the rate of cardiac arrests before procurement completion (from 28% to 26%), an increase in notifications per million (from 172 [24/million] to 327 [46/million]), effective donors per million (from 12 [1.7/million] to 28 [3.9/million]), organ transplants per million (from 27 [3.9/million] to 62 [8.7/million]), corneal transplants per million (from 133 [18.6/million] to 255 [35/million]), and number of active CIHDOTTs and OPOs (from 3/0 to 10/1). These findings demonstrate marked growth and improvement in the regional transplant system.Conclusion: This study demonstrates that the implementation of the Transplant Acceleration Program (PAT-MA) had a positive impact on key performance indicators at the Maranho Transplant Center. The results underscore the importance of strategic management approaches to optimize transplant program outcomes.
Keywords: Quality improvement; brazil; organ transplantation; management program; PAT-MA; health systems; Maranh